Pendampingan Kader Dalam Pemantauan Balita Salit Melalui Buku Kia Di Desa Tarus Kabupaten Kupang - Adriana M. S Boimau; Tirza Vivianri Isabela Tabelak; Serlyansie V. Boimau; Agustina Abuk Seran (Universitas Merdeka Surabaya, 2024)
involvement of cadres, mothers and families in monitoring the health and growth and development of babies and toddlers is very important. Cadres, mothers and families are the first people to assist and help babies and toddlers. Monitoring babies and toddlers by cadres is very useful for screening children's conditions every day. If a child is in trouble or sick, immediately take him or her to a health worker or provide first action to reduce pain and even prevent the death of a toddler. The aim of this community service is to empower women, namely cadres, through training in daily monitoring of the growth and development of babies under five in Tarus Village, Central Kupang District, Kupang Regency. The methods used are lectures, training and mentoring related to daily monitoring of the growth and development of babies under five using the latest 2021 edition of the MCH book. In the 2021 MCH book there are daily monitoring instruments for babies 0-60 days and daily monitoring instruments 2-60 months. 85% of the cadres in Tarus Village who are involved in education and monitoring children's growth and development are aged 30-50 years. Cadres' knowledge about the growth and development of babies under five is minimal even though they are provided with MCH books. Community service activities include education and assistance in monitoring the growth and development of babies under five. There is an increase in cadres' knowledge and abilities regarding growth and development.